Robust Control of Fluidized Bed Layering Granulation. Issue 2 (2020) - Neugebauer, Christoph; Seidel, Carsten; Palis, Stefan; Kienle, Achim
Abstract: This contribution is concerned with control of fluidized bed layering granulation with external sieve-mill-cycle. It is well-known that this configuration is sensitive with respect to variations in the operating conditions and supplied material properties. Therefore, control is needed to achieve desired particle properties over a wide range of process conditions. In this contribution H∞ -control is applied in order to control the process. In contrast to preceding works, the coupling between the particle and the fluid phase is taken into account. Furthermore, in addition to the Sauter diameter of the particle size distribution, the apparent particle porosity is controlled, which is of great importance for practical applications.